International Convention Vs National Interest: Contestation among Indonesian Government Institutions on Underwater Cultural Heritage Conservation - Rahardjo, Supratikno (Indonesian Journal of International Law, 2019)
Indonesia’s underwater cultural heritage has tremendous potential to enhance the understanding of Indonesia’s maritime culture history. But, this cultural heritage has a vulnerability due to various factors that can cause cultural heritage to be extinct. Indonesia’s vast waters have substantial underwater heritage, but the government has constraints to ensure its protection. In Indonesia, the authority for underwater cultural resources found in the sea involves two government agencies that have different views on the underwater cultural heritage. On one hand, the cultural heritage is treated as “cultural goods” and on the other hand it is treated as “economic goods”. The first purpose-protected perspective is supported by the law on cultural preservation and the principles agreed upon in the international convention on the protection of underwater cultural heritage. While the second perspective is supported by the presidential decree that is based on the national interest to improve the welfare of the community. This article explains how the two government institutions are trying to compete and negotiate to win their respective agendas.